DISCOURSE ON SEXUAL VIOLENCE AND GENDER INEQUALITY IN THE PALESTINIAN-ISRAELI CONFLICT: SARA MILLS’ CRITICAL DISCOURSE ANALYSIS - Aulia Sirait, Nurul; Zawawi, Moh (JURNAL KONFIKS, 2025)
This study examines the discourse of sexual violence and gender inequality against Palestinian women in the Palestine–Israel conflict using Sara Mills’ Critical Discourse Analysis approach. It aims to reveal how women’s positions are represented in Arabic online media Al Arabiya, Al Jazeera, and CNN Arabic. The research employs a qualitative descriptive method, analyzing ten news texts based on four key elements of Mills’ framework: the subject, object, writer, and reader positions. The findings show that Palestinian women experience multiple layers of oppression. They are victims of sexual violence, harassment, humiliation, and murder by Israeli forces, while also facing structural inequality such as limited access to reproductive health and basic needs. Al Arabiya portrays women as powerless victims, Al Jazeera provides space for women to speak as active subjects, while CNN Arabic presents their suffering collectively but often conceals the perpetrators through passive constructions. These findings highlight that the Palestine Israel conflict is not merely political or military but also a gendered media issue, where women are symbolized as powerless sufferers. Thus, media discourse plays a crucial role in shaping public awareness of justice and gender equality for Palestinian women.